ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS BANK PEMBIAYAAN RAKYAT SYARIAH (BPRS) DI INDONESIA PASCA KRISIS KEUANGAN GLOBAL TAHUN 2008 - Fasiha Kamal (MUAMALAH, 2014)
BPR sharia as a financial institution must be able to carry out the functions and duties well, especially in terms of capability and effectiveness of the company's performance relating to financial and bank soundness as measured by financial ratios. Based on the above, this study used financial ratios to measure the performance of BPRS related to the profitability of the ROA.Therefore, the formulation of the problem in this recent research are: what factors financial ratios (NPF, FDR, CAR, and ROA) the effect on profitability as measured by ROA BPRS ?. The results of the study are: Simultaneously four variables (FDR, NPF, CAR, and ROA) ROA effect on rural banks Sharia. While partially shows that the Capital Adequacy Ratio (CAR), an effect on ROA.Financing to Deposit Ratio (FDR), Non Performing Financing (NPF), and Operating Costs Operating Income (ROA) partially no effect on ROA of Islamic rural banks. Predictive ability of the four variables on ROA of Islamic rural banks by 55% while the remaining 45% is influenced by other factors not included in our model.